Folklore in China: Past, Present, and Challenges - Juwen Zhang (Humanities, 2018)
This article first outlines the long history of folklore collection in China, and then describes the disciplinary development in the 20th century. In Section 3, it presents the current situation in terms of disciplinary infrastructure, development, contribution, and challenge, with a focus on the recent practice of safeguarding Intangible Cultural Heritage. These accounts are largely based on the views of the Chinese folklorists. In the final section, this article discusses the issues of cultural continuity, integration, and self-healing mechanisms in Chinese culture by putting Chinese folkloristics in a historical and world perspective. This paper suggests that, to understand Chinese folklore and culture, one must be aware of the most basic differences between Chinese fundamental beliefs and values and those of the West, and that Chinese folklore and folkloristics present new challenges to the current paradigms put forward in the post-colonial, post-modern, and imperial ideologies.